Efektivitas e-LKPD Berbasis keterampilan Proses Sains Pada materi Semester I Kelas XI SMA/MA - Suhardi Aldi; Adnan; Ismail (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: Test the effectiveness of electronic student worksheets (e-LKPD). The hope of this research is to test the effectiveness of e-LKPD based on science process skills. The type of this research is research and development which refers to the type of ADDIE development (Analysis, Design, Development, Implementation, and Evaluation). The resulting product is an e-LKPD based on science process skills (KPS), which is carried out effectively by 28 students. The instrument used is a multiple choice test. The instrument that has been developed is used for data collection. The resulting data is then analyzed quantitatively. Based on the results of the study, it is illustrated that the level of effectiveness of the KPS-based e-LKPD in terms of student learning outcomes is 0.7 which is in the effective category with a moderate level. So that the PPP-based e-LKPD is effective at a moderate level.